Analyze and Identify Peiminine Target EGFR Improve Lung Function and Alleviate Pulmonary Fibrosis to Prevent Exacerbation of Chronic Obstructive Pulmonary Disease by Phosphoproteomics Analysis - Ma, Xiaoyao; Liu, Aina; Liu, Wenjuan; Wang, Zhihua; Chang, Nianwei; Li, Suyun; Li, Jiansheng; Hou, Yuanyuan; Bai, Gang (Frontiers in Pharmacology, 2019)
Chronic obstructive pulmonary disease (COPD) has been a major public health problem and is still a formidable challenge for clinicians. It is urgent to find new compounds for minimizing the risk of disease progression and exacerbation especially in the early phase of COPD. A traditional Chinese medicine (TCM) formula, Chuan Bei Pi Pa dropping pills (CBPP), was tested in this study to investigate its potential mechanisms in preventing the exacerbation of COPD. Phosphoproteomics analysis for a smog stimulated early stage COPD mice model was employed to detect the underlying molecular mechanisms of CBPP. In addition, protein–protein interaction (PPI) and bioinformatics analyses were included to analyze the key proteins and predict the key bioactive compounds. The results indicated that peiminine (PEI) target epidermal growth factor receptor (EGFR) prevented the exacerbation of COPD by inhibiting the EGFR signaling pathway, and ursolic acid (UA) can alleviate inflammation disorders via inhibition of CASP3 on mitogen-activated protein kinase (MAPK) signaling pathway. After in vivo and in vitro evaluations, we revealed that PEI from CBPP, as a lead compound, can improve lung function and alleviate pulmonary fibrosis by acting on the EGFR and MLC2 signaling pathways. Furthermore, the approach described here is an effective way to analyze and identify the bioactive ingredients from a mixture by functional proteomics analysis.